2021
DOI: 10.3390/antibiotics10070776
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Antibiotic Resistant Escherichia coli in Sarawak Rivers and Aquaculture Farms, Northwest of Borneo

Abstract: Background: The emergence of plasmid-mediated antibiotic resistance in Escherichia coli in water resources could pose a serious threat to public health. The study aims to investigate the dispersion of plasmid-mediated antibiotic-resistant E. coli from six rivers in Sarawak and two aquaculture farms in Borneo. Methods: A total of 74 water samples were collected for the determination of their bacteria colony count. An IMViC test identified 31 E. coli isolates and tested their susceptibility against twelve clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…The result was in agreement with Turnipseed et al (2018), who detected a high level of amoxicillin residue in catfish, trout, and even in salmon farms by liquid chromatography high-resolution mass spectrometry (LC-HRMS) screening in Europe. 85.3% of amoxicillin resistant E. coli detected in the study was lower as compared to Lihan et al (2021), who stated 100% amoxicillin resistance detected in E. coli isolated from aquaculture farms in…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The result was in agreement with Turnipseed et al (2018), who detected a high level of amoxicillin residue in catfish, trout, and even in salmon farms by liquid chromatography high-resolution mass spectrometry (LC-HRMS) screening in Europe. 85.3% of amoxicillin resistant E. coli detected in the study was lower as compared to Lihan et al (2021), who stated 100% amoxicillin resistance detected in E. coli isolated from aquaculture farms in…”
Section: Resultsmentioning
confidence: 54%
“…Thiang et al ( 2021) indicated a wide distribution of antibiotics used in most aquaculture farms in Malaysia and become a resistance hotspot in promoting the growth of antibiotic resistant bacteria. Antibiotics residue in manure and other waste-based fertilizers may run off into waterways by exchanging resistance genes and altering the microbial community in water and sediment (Lihan et al, 2021). Thus, it may contribute to antibiotic resistance bacteria cases in our study.…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 86%
See 1 more Smart Citation
“…According to the study of Ng et al (47), it was found that 33 multi-drug-resistant E. coli were isolated from surface waters in aquaculture sites of Singapore. Lihan et al (48) investigated the antibiotic-resistant E. coli from Sarawak rivers and aquaculture farms in northwest of Borneo. They found that resistance to piperacillin (100%) was observed in all E. coli isolates, resistance to amoxicillin (100%) and ampicillin (100%) was observed in E. coli isolated from aquaculture farms, and resistance to streptomycin (93%) was observed in E. coli isolated from rivers.…”
Section: Discussionmentioning
confidence: 99%
“…industry, sewage, dams etc.) (Martin et al, 2018;Prabakaran et al, 2020;Lihan et al, 50 2021; Liong et al, 2021). Enhanced sediment delivery to rivers and coasts results in decreased light availability through increased turbidity and light attenuation (Storlazzi et al, 2015).…”
mentioning
confidence: 99%